Sekolah Radja "Kweekschool Fort de Kock": Exploring History and Role in Teacher Education in the Netherlands East-Indies - Putra, Purwanto; Hendrawan, Muhammad Rosyihan; Oktaria, Renti; Gunawan, Gunawan (Educative: Jurnal Ilmiah Pendidikan, 2024)
This research aims to analyze the background and history of establishment, contributions, and educational impacts of the presence of the "School Radja," Kweekschool Fort de Kock, on indigenous students in the Dutch East Indies. The method employed is historical methodology, involving the collection, analysis, and interpretation of various historical sources related to the Kweekschool Fort de Kock school with new perspectives on methodology, methods, theories, and themes in historical research, social sciences, and particularly education. The findings indicate that the establishment of Kweekschool Fort de Kock was part of Dutch colonial efforts to educate and control the indigenous population in the Dutch East Indies. This school provided teacher education for indigenous students with the aim of creating educators loyal to the colonial government. In conclusion, the existence of Kweekschool Fort de Kock played a significant role in the history of education in the Dutch East Indies, aiming to educate the nation's children but also reflecting the dynamics of colonial power influencing the education process and cultural identity of indigenous students. This study underscores the importance of understanding the historical context of colonial education in evaluating the educational legacy left behind and its impact on indigenous communities.